MILLENNIALS EMPLOYEES’ WORK ENGAGEMENT: THE INFLUENCE OF EMPOWERING LEADERSHIP, SELF-EFFICACY AND WORK MEANINGFULNESS - Alamudi, Abdul Kadir (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
The study was conducted to analyze and prove whether there is an influence of empowering leadership and self-efficacy on employees’ work engagement with work meaningfulness as a mediating variable in wood processing employees of the particle board division in Probolinggo, East Java. The type of research uses explanatory research methods, survey methods, and approaches used quantitively and data was collected using questionaires on 165 employees. The data has been collected, then tested using Structural Equation Model (SEM) method in the SmartPLS3 program application. It was found that the result of the study found that empowering leadership had an insignificant effect on work engagement, while self-efficacy and work meaningfulness had a positive and significant effect on work engagement. Empowering leadership and self-efficacy also have a positive and significant effect on work meaningfulness. Work meaningfulness is able to mediate the influence of empowering leadership and self-efficacy on work engagement positively and significantly.